If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -1(4x + -6) = 62 Reorder the terms: 11x + -1(-6 + 4x) = 62 11x + (-6 * -1 + 4x * -1) = 62 11x + (6 + -4x) = 62 Reorder the terms: 6 + 11x + -4x = 62 Combine like terms: 11x + -4x = 7x 6 + 7x = 62 Solving 6 + 7x = 62 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 7x = 62 + -6 Combine like terms: 6 + -6 = 0 0 + 7x = 62 + -6 7x = 62 + -6 Combine like terms: 62 + -6 = 56 7x = 56 Divide each side by '7'. x = 8 Simplifying x = 8
| j+13=-3 | | -60=-3(4+6n)+2(5n+4) | | F(v-2)=6x+7 | | 3+n=-7 | | X^2-9y^2+2x-54y-98=0 | | 7+k=42 | | .5(ab)=.3a | | 4(x+6)-11=25 | | 2-(x+3)=-2x+5 | | X^2-9y+2x-54y-98=0 | | 3x+35=90 | | 9x-55=90 | | 117+105+112+x=115 | | a-b=-0.9 | | 2a+6=3-.2a | | 5x+x-20+2=180 | | 2b+2a=3 | | 12-8x=3x-21 | | 8x^2+14x+17= | | 0.893=2.61x-2.52 | | 2d-6=8 | | 48+.99=1.29n | | 48+99n=1.29n | | 3x+12-5x=2(x-3) | | -2(-k-12)=-2k-12 | | 2(m-6)-7(7m-5)=23 | | 0.5p+4=2(p+2) | | 0.5p+4=(p+2) | | 87=3(6m-1) | | 6x+12+16x+4+18x+4=180 | | 6x+4=(7x+1)2 | | 48=-8(-3-3z) |